2019
DOI: 10.1891/0730-0832.38.4.206
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Early Language and Literacy Program for Parents of Infants in the NICU

Abstract: PurposeTo evaluate the effect of a NICU parent education program on parents' early language and literacy practices, and on their confidence interpreting and responding to infant signals.DesignSingle group, pre- and post-test, mixed-methods evaluation design.SampleOne hundred and four parents and other caregivers completed questionnaires before and after the one-hour program. Ten parents participated in follow-up interviews.Main Outcome VariablesBefore and after sessions, participants reported on frequency of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…A spontaneous preterm birth is a birth that begins on its own and that happens when a woman enters prema-ture labor or when her water breaks too early. Most preterm births occur spontaneously, but some are caused by the early induction of labor or caesarean section, whether for medical or nonmedical reasons [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…A spontaneous preterm birth is a birth that begins on its own and that happens when a woman enters prema-ture labor or when her water breaks too early. Most preterm births occur spontaneously, but some are caused by the early induction of labor or caesarean section, whether for medical or nonmedical reasons [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Another limitation of this study relates to the absence of data about how and how often parents read to their infants after hospital discharge. If previous studies [69,70,73,74] have indeed shown that book-reading interventions are effective for improving parental attitudes towards reading at home, as well as improving how often parents read to their infants, an accurate measure of these dimensions would have strengthened our findings. The reported results should thus be considered cautiously, with future investigation recommended to consider these variables.…”
Section: Limitations and Strengthsmentioning
confidence: 50%
“…Positive benefits of book-reading interventions on linguistic skills were also observed in samples of preterm infants [69,70], although these studies assessed interventions implemented in the second year of infant life and did not consider the effects of early infant exposure to book-reading. A separate line of studies investigated the feasibility of book-reading intervention in the context of the NICU, finding that it is well-accepted by parents and not intrusive [56,71,72]; moreover, it was found to be associated with improvements in parental knowledge about when and how to read to their infant [73], and in their attitudes towards this reading practice [74]. Nevertheless, these studies did not assess possible effects on infant language skills.…”
Section: Introductionmentioning
confidence: 99%
“…Early shared reading experiences in infancy have been shown to develop a child's emergent literacy 19 . Reading provides a means of increasing adult word exposure and improving parent–infant interactions 20,21 . Few studies have examined language benefits of reading and infant‐directed speech on preterm infant early language development 21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…19 Reading provides a means of increasing adult word exposure and improving parent-infant interactions. 20,21 Few studies have examined language benefits of reading and infant-directed speech on preterm infant early language development. 21,22 Reading is encouraged in the newborn period by general paediatricians and programmes such as Reach Out and Read; however, little is known about the impact of reading to preterm infants hospitalised in the NICU.…”
mentioning
confidence: 99%